Effects of successive annual training on aerobic endurance indices in young swimmers - Arsoniadis, G. G.; Botonis, P. G.; Nikitakis, I. S.; Kalokiris, D.; Toubekis, A. G. (The Open Sports Sciences Journal, 2017)
Background: The magnitude of long-term changes on aerobic endurance indices provides useful information for understanding any training-induced adaptation during maturation. Objective: The aim of the present study was to compare changes in different aerobic endurance indices within two successive training years. Methods: Eight swimmers, (five male, three female; age: 14.1±1.5, height: 163.8±9.9 cm, body mass: 55.8±10 kg) were tested at four time-points, before and after the 12-week specific preparation period, within two successive training years (at year-1: start-1, end-1, at year-2: start-2, end-2). In each time-point were timed in distances of 50, 200 and 400 m front crawl to calculate the critical speed (CS). Subsequently, performed 5x200 m front crawl progressively increasing intensity and the lactate concentration was determined after each repetition. Using the individual speed vs. lactate concentration curve, the speed corresponding to 4 mmol.L-1 concentration (V4) and the speed corresponding to lactate threshold (sLT) were calculated. Results: Aerobic endurance was increased from year-1 to year-2 (effect of time, p<0.05) and no difference was observed between V4, sLT and CS at all time-points of evaluation (p>0.05). In year-1, V4, sLT and CS were unchanged even after the 12-week period (p>0.05). During year-2 of training it was only V4 that was increased from start-2 to end-2 (p<0.05), whereas sLT and CS were unchanged at the same period (p>0.05). Conclusion: The aerobic endurance indices change similarly throughout a two-year training, independent of the maturation. Possibly, V4 is more sensitive to detect training adaptations during the specific preparation period in young swimmers.